Climate change and labour : the need for a "just transition" (International journal of labour research ;, 2010)
Climate change is now widely acknowledged as one of the great - if not the greatest - challenges facing humanity in the coming decades. Through its impact on average temperature, precipitations and sea levels, it will endanger the livelihood of hundreds of millions and impose increasing costs on our societies if nothing is done.